The effect of motivation and commitment organization on employee performance: Case study of PT. PLN (PERSERO) Bantar Gebang, Bekasi - Isyana Emita; Syamsudin; Otto Siregar (Journal of Economics and Business Letters, 2021)
Performance means that work will occur in terms of quality as well as quantity achieved by an employee in carrying out his duties following the responsibilities given to him. In building good performance, the factors that are claimed to be important are work motivation and work discipline. The purpose of this study is to determine and analyze the effects of work motivation and organizational commitment on the performance of employees of PT. PLN (Persero) Bantar Gebang, Bekasi. This study uses the HRM theory related to employee performance, work motivation, and organizational commitment. The research uses quantitative methods using an associative approach. The sample used in this study means that 35 people use a saturated sample. Data collection techniques used are interviews and questionnaires consisting of validity and reliability tests. The data analysis technique used is the Multiple Linear Regression Test, and the Classical Estimation Test consisting of normality, multicollinearity, heteroscedasticity tests. The hypothesis consists of the origin of the t-test, f test, and coefficient of determination. The results of this study share that the work motivation variable (XI) has a positive and significant effect on the performance of employees of PT. PLN (Persero) Bantar Gebang, Bekasi, as evidenced by the t arithmetic value for the motivation variable (X1) as much as 2.740 and the value in the 5% distribution as much as 2.034 then t-count 2.740 > t-table 2.034 and also the value is significantly smaller than 0.05 (0.001 <0.05), meaning that there is a significant influence between motivation on employee performance. The calculated F value is greater than the F table value, namely F arithmetic 22.229 > F table 3.28 and also the value is significantly smaller than 0.05, namely 0.000 < 0.05. This means that the variables of motivation and work discipline together (simultaneously) have a positive and significant influence on employee performance originating that there will be a t-test with a t-count of five,431 while t-table is 2,005 and has a significant number of 0.000 <0.05 Ho is rejected. From the result of testing the work discipline variable (X2), it indicates that discipline has a positive and significant effect on the performance of PDAM Tirtanadi employees, Tuasan Medan Branch, as evidenced by the results of the t-test using t-count as much as 3.473 while t-table is 2.005 and has a significant number of 0.001 <0.05 Ho rejected, where F-count 92.868 > 3.18 F-table. Furthermore, the value of R Square in the regression model is 0.582, or 58.2% of employee performance is explained by the variables of work motivation (XI) and organizational commitment (X2), and 41.5% is explained by other factors not examined.